Minimal clinical data sets for spine-related musculoskeletal disorders in primary care and outpatient settings: a scoping review protocol - Pierre Côté; Andrea C Tricco; Cesar A Hincapié; Léonie Hofstetter; Jérémie Mikhail; Isabelle Pagé (BMJ Open)
Introduction Lack of standardised clinical data collection may lead to reduced quality in musculoskeletal (MSK)-related clinical care and research. Little is known about the availability and characteristics of minimal clinical data sets for spine-related MSK disorders in primary care and outpatient settings and their utility for improving healthcare quality. Our objective is to undertake a scoping review aiming to identify and map current literature on minimal clinical data sets for measuring and monitoring health status in patients with spine-related MSK disorders in primary and outpatient healthcare settings.Methods and analysis The 2020 Joanna Briggs Institute methodology for scoping reviews will guide review conduct. The review will consider studies that describe and report on minimal clinical data sets for spine-related MSK disorders designed for primary care and outpatient clinical practice settings. Quantitative and qualitative study designs will be eligible, including consensus-based studies, interventional, observational, feasibility and linguistic validation studies. Studies published in English, German, French, Italian and Spanish will be included, with no limit on date of publication. MEDLINE, CINAHL, Cochrane Library, Index to Chiropractic Literature, MANTIS, ProQuest Dissertations & Theses Global and medRxiv preprint repository will be searched from database inception to 25 July 2021. Two reviewers will independently screen identified titles, abstracts and relevant full-text records, and then extract data using review-specific data extraction forms. Findings will be synthesised and presented as a descriptive summary using PRISMA ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews).Ethics and dissemination Ethics review and approval is not required for this scoping review. Our target audience for this review will be clinicians, researchers, patients and other relevant stakeholders involved in the measurement and health status monitoring of patients with spine-related MSK disorders. Results will be shared through peer-reviewed publication and presentations at relevant conferences.Protocol registration number https://osf.io/fkw5b.